First-in-human DR5 PET reveals insufficient DR5 expression in patients with gastrointestinal cancer - Feng Wang; Yan Zhang; Hua Zhu; Jin Ding; Nan Li; Tong Zhou; Jun Zhao; Zhi Yang; Yingjie Li; Xinyu Wang; Yunfeng Yao; Shujing Wang; et al. (Journal for ImmunoTherapy of Cancer)
Background Death receptor 5 (DR5) is a promising therapeutic target for cancer therapy. However, many clinical trials of DR5 agonists failed to show significant therapeutic efficacy in patients with cancer. The study aimed to investigate the feasibility of using 89Zr-CTB006 positron emission tomography (PET) for noninvasive imaging of DR5 expression in preclinical models and patients with gastrointestinal (GI) cancers.Methods Balb/c, Sp2/0 xenograft and patient-derived tumor xenograft were employed for micro-PET/CT imaging in vivo. In the clinical study, patients with GI cancers planning to undergo surgical operation were enrolled and underwent 18F-FDG and 89Zr-CTB006 PET/CT. The tumor tissues were obtained through surgical operation and DR5 expression levels were confirmed by RNAscope.Results Preclinical studies showed that 89Zr-CTB006 PET could specifically detect DR5 expression levels in vivo. Twenty-one patients, including nine gastric cancers and 12 colorectal cancers, were enrolled. The biodistribution showed high uptake in the liver and spleen and low uptake in the brain, lung and muscle with an acceptable whole-body dosimetry of 0.349 mSv/MBq. Strikingly, the adrenal glands maintained stable high uptake over the entire examination in all patients. The tumor lesions showed different levels of uptake of 89Zr-CTB006 with a mean maximum standardized uptake value (SUVmax) of 6.63±3.29 (range 1.8–13.8). Tumor tissue was obtained from 18 patients, and 89Zr-CTB006 uptake in patients with RNAscope scores of 3–4 was significantly higher than that in patients with scores of 0–2. An SUVmax of 9.3 at 48 hours and 6.3 at 72 hours could be used to discriminate the DR5 expression status of tumors both with a sensitivity and specificity of 100% and 92.9%, respectively.Conclusions 89Zr-CTB006 PET/CT is capable of detecting DR5 expression in cancer patients and is a promising approach to screen patients with DR5 overexpression.